2009
DOI: 10.1097/qad.0b013e32832ec20d
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding with maternal antiretroviral therapy or formula feeding to prevent HIV postnatal mother-to-child transmission in Rwanda

Abstract: : Maternal HAART while breastfeeding could be a promising alternative strategy in resource-limited countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 25 publications
5
83
1
2
Order By: Relevance
“…Actualmente algunas investigaciones han demostrado que junto al uso materno de anti-retrovirales (ARV) el amamantamiento sería posible. Desde un enfoque de riesgo, en países donde la morbi-mortalidad infantil en ausencia de lecha materna es elevada, es aconsejable preservar la lactancia natural 11,12 . En 1994 Connors y cols., demostraron que el tratamiento con zidovudina (ZDV) a la mujer durante el www.sochinf.cl…”
Section: Introductionunclassified
“…Actualmente algunas investigaciones han demostrado que junto al uso materno de anti-retrovirales (ARV) el amamantamiento sería posible. Desde un enfoque de riesgo, en países donde la morbi-mortalidad infantil en ausencia de lecha materna es elevada, es aconsejable preservar la lactancia natural 11,12 . En 1994 Connors y cols., demostraron que el tratamiento con zidovudina (ZDV) a la mujer durante el www.sochinf.cl…”
Section: Introductionunclassified
“…WHO guidance remains that in countries where formula feeding is safe, a national or regional policy decision should be made on feeding policy [300]. Although breastfeeding transmission is reduced by ART, it is not abolished [78,293,[295][296][297]301,302]. There is laboratory evidence that the breast milk of HIV-positive women on ART contains cells that may shed virus [303].…”
Section: Infants Born To Hiv-positive Mothers Should Follow the Routimentioning
confidence: 99%
“…Recently, cohort [293][294][295][296] and RCT [66,78,297] data from Africa have shown that ART can significantly reduce the risk of HIV transmission from breastfeeding. This is in settings where breastfeeding is not affordable, feasible, acceptable, sustainable and safe, and mortality from formula feeding outweighs additional mortality from HIV transmission by breastfeeding [298,299].…”
Section: Infants Born To Hiv-positive Mothers Should Follow the Routimentioning
confidence: 99%
“…[39][40][41][42][43][44][45] The estimated cumulative probability of postnatal transmission of HIV in these cohorts is 0.5-3% at 6-9 months of age. 39,[42][43][44] Breastfeeding reduces infant morbidity and mortality, protects against childhood infections and promotes child spacing. In resource-poor countries mothers often have no access to clean water or formula for safe replacement feeding.…”
Section: Infant Feedingmentioning
confidence: 99%